Design of Compact UWB Antenna with Single, Dual and Triple Band-Notched Characteristics Utilizing Split Ring Resonator - Swelam, W.; Wahab, M. G.; Abd ElAzeem, M. H. (Journal of Advanced Research in Applied Mechanics, 2020)
A novel compact antenna for Ultra-Wideband (UWB) applications; design is being presented in this paper. The proposed design is fed using 50 ohm coplanar waveguide (CPW). A spacious impedance bandwidth is enacted covering the band from 3.1 GHz to more than 20 GHz with reflection coefficient superior to -10dB. Triple frequency notches are realized in order to assure coexistence with the narrow band applications allocating some of these frequency bands of WiMAX, WLAN and X-band satellite communication. Split ring resonator (SRR) is engraved in coplanar ground for both frequency bands rejection of IEEE 802.16 WiMAX (3.3-3.8 GHz) and IEEE 802.11 WLAN (5.15-5.825 GHz). Folded slot is etched in feed line for frequency band rejection of (7.25–8.395) GHz for X-band satellite communication. The suggested antenna has a total size of 24 × 18.5 × 1.5 mm3. Omnidirectional radiation pattern with stable radiation characteristics is realized. Advantageous reconciliation is enacted between simulated and measurement consequence. To scrutinize the depiction of the prospective antenna in terms of attaining wideband operations, the commercially available simulation software CST STUDIO SUITE ver.2014 is adopted for numerical analysis.